(untitled) (Global Journal of Science Frontier Research, 2015)
The usefulness of cassia podocarpa as locally antifungal agent necessitated the qualitative and quantitative determination of the phytochemicals present.The screening of the leaf and flower showed the presence of flavonoid, tannin, saponin, alkaloid and glycoside. The quantitative analysis showed that the flavonoid in the leaf (6.73 mg/g)was more than that of the flower (5.83mg/g). Also, the tannin in the leaf (10.11mg/g) doubled that of the flower (5.24mg/g).The saponin content in the leaf (27.36mg/g) was higher than that of the flower (13.91mg/g). The alkaloid content in the leaf (19.70mg/g) was more than that of the flower (6.59mg/g). However the glycoside of leaf (7.10mg/g) was just little bit higher than that of flower (6.32mg/g). From the quantitative evaluation of the leaf and flower of this plant, this has really confirmed the local use in the treatment of eczema in human body when the liquid is being extracted and the plant is a reservoir of many novel compounds which can be of immense use to the pharmaceutical world.